Guided bone regeneration with local zoledronic acid and titanium barrier: An experimental study - Dundar, Serkan; Ozgur, Cem; Yaman, Ferhan; Cakmak, Omer; Saybak, Arif; Ozercan, Ibrahim Hanifi; Nacakgedigi, Onur (Spandidos Publ Ltd, 2016)
The aim of this study was to evaluate the effects on new bone formation of autogenous blood alone or in combination with zoledronic acid (ZA), a -tricalcium phosphate (-TCP) graft or ZA plus a -TCP graft placed under titanium barriers. For this purpose, eight adult male New Zealand white rabbits were used in the study, each with four titanium barriers fixed around four sets of nine holes drilled in the calvarial bones. The study included four groups, each containing 2 rabbits. In the autogenous blood (AB group), only autogeneous blood was placed under the titanium barriers. The three experimental groups were the AB+ZA group, with autogenous blood plus ZA, the AB+-TCP group, with autogeneous blood plus a -TCP graft, and the AB+-TCP+ZA group, with autogeneous blood plus a -TCP graft and ZA mixture under the titanium barriers. The animals were sacrificed after 3 months. The amounts of new bone formation identified histomorphometrically were found to be higher after 3 months than at the time of surgery in all groups. The differences between the groups were examined with histomorphometric analysis, and statistically significant differences were identified at the end of the 3 months. The bone formation rate in the AB+-TCP+ZA group was determined to be significantly higher than that in the other groups (P<0.05). In the AB+ZA and AB+-TCP groups, the bone formation rate was determined to be significantly higher than that in the AB group (P<0.05). No statistically significant difference in bone formation rate was observed between the AB+-TCP and AB+ZA groups. Local ZA used with autogeneous blood and/or graft material appears to be a more effective method than the use of autogeneous blood or graft alone in bone augmentation executed with a titanium barrier.
Keywords: guided bone regeneration; zoledronic acid; titanium barrier; rabbit calvarium